The Effect of Contact Time and Optimum pH on the Adsorption of Methylene Blue Dye by Alginate-Chitosan Complex Polyelectrolyte Films - Rahayu Rahayu; Samsul Nurlette; Anselmus Boy Baunsele (Department of Chemistry - Universitas Bangka Belitung, 2023)
Alginate derived from brown seaweed (Padina.sp) can be combined with chitosan to form a complex polyelectrolyte film, which can be used as an adsorbent for water contaminants such as methylene blue dye. The adsorption process is carried out by determining the maximum wavelength, which is then used to determine the contact time and pH needed to adsorb methylene blue. The results showed that the optimum contact time required to adsorb methylene blue was 20 minutes with an adsorption capacity of 18.8055 mg/L, and the optimum pH occurred at pH 9 with an adsorption capacity of 21.9975 mg/L.